Droplet detachment and pinch-off of bidisperse particulate suspensions. Issue 25 (8th June 2021) - Thiévenaz, Virgile; Rajesh, Sreeram; Sauret, Alban
Abstract : Solid particles dispersed in a liquid phase modifies the pinch-off of droplets. Compared to monodisperse particles, a bimodal distribution reduces the viscosity for a given volume fraction and makes the detachment process faster. Abstract : When a droplet is generated, the ligament connecting the drop to the nozzle thins down and eventually pinches off. Adding solid particles to the liquid phase leads to a more complex dynamic, notably by increasing the shear viscosity. Moreover, it introduces an additional length scale to the system, the diameter of the particles, which eventually becomes comparable to the diameter of the ligament. In this paper, we experimentally investigate the thinning and pinch-off of drops of suspensions with two different sizes of particles. We characterize the thinning for different particle size ratios and different proportions of small particles. Long before the pinch-off, the thinning rate is that of an equivalent liquid whose viscosity is that of the suspension. Later, when the ligament thickness approaches the size of the large particles, the thinning accelerates and leads to an early pinch-off. We explain how the bidisperse particle size distribution lowers the viscosity by making the packing more efficient, which speeds up the thinning. This result can be used to predict the dynamics of droplet formation with bidisperse suspensions.